Joining aluminum alloy to ultrahigh-strength boron steel through an impact welding approach. (August 2020) - Kapil, Angshuman; Thurston, Brian; Vivek, Anupam; Daehn, Glenn
Abstract: Direct welding of ultrahigh-strength boron steels to aluminum alloys is challenging but of great practical importance. The present study reports a new approach in vaporizing foil actuator welding to produce direct spot welds between 6022-T4 Al alloy and Usibor 1500®, a representative boron steel. Mechanical testing results revealed a strong joint with failure occurring at the Al base metal outside the weld nugget. Comparison of joint strengths with other joining techniques revealed performance on par if not better, opening prospects for development of more robust dissimilar welding pairs in the future.